Discrete-continuum multiscale model for transport, biomass development and solid restructuring in porous media. (September 2017) - Ray, Nadja; Rupp, Andreas; Prechtel, Alexander
Highlights: We present a process-based mathematical model related to microaggregate development in soils. The algorithm links discrete cellular automaton methods with continuous partial differential equations at two scales. Simulations show combined effects of reactive transport, biomass development, and restructuring of soil particles. Abstract: Upscaling transport in porous media including both biomass development and simultaneous structural changes in the solid matrix is extremely challenging. This is because both affect the medium's porosity as well as mass transport parameters and flow paths. We address this challenge by means of a multiscale model. At the pore scale, the local discontinuous Galerkin (LDG) method is used to solve differential equations describing particularly the bacteria's and the nutrient's development. Likewise, a sticky agent tightening together solid or bio cells is considered. This is combined with a cellular automaton method (CAM) capturing structural changes of the underlying computational domain stemming from biomass development and solid restructuring. Findings from standard homogenization theory are applied to determine the medium's characteristic time- and space-dependent properties. Investigating these results enhances our understanding of the strong interplay between a medium's functional properties and its geometric structure. Finally, integrating such properties as model parameters into models defined on a larger scale enables reflecting the impact of pore scale processes on the larger scale.